Comprehensive Guide to Extracting and Expressing Fungal Secondary Metabolites with Aspergillus fumigatus as a Case Study. Issue 12 (27th December 2021) - Nickles, Grant; Ludwikoski, Isabelle; Bok, Jin Woo; Keller, Nancy P.
Abstract: Fungal secondary metabolites (SMs) have captured the interest of natural products researchers in academia and industry for decades. In recent years, the high rediscovery rate of previously characterized metabolites is making it increasingly difficult to uncover novel compounds. Additionally, the vast majority of fungal SMs reside in genetically intractable fungi or are silent under normal laboratory conditions in genetically tractable fungi. The fungal natural products community has broadly overcome these barriers by altering the physical growth conditions of the fungus and heterologous/homologous expression of biosynthetic gene cluster regulators or proteins. The protocols described here summarize vital methodologies needed when researching SM production in fungi. We also summarize the growth conditions, genetic backgrounds, and extraction protocols for every published SM in Aspergillus fumigatus, enabling readers to easily replicate the production of previously characterized SMs. Readers will also be equipped with the tools for developing their own strategy for expressing and extracting SMs from their given fungus or a suitable heterologous model system. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Making glycerol stocks from spore suspensions Alternate Protocol 1 : Creating glycerol stocks from non‐sporulating filamentous fungi Basic Protocol 2 : Activating spore‐suspension glycerol stocks Basic Protocol 3 : Extracting secondary metabolites from Aspergillus spp grown on solid medium Alternate Protocol 2 : Extracting secondary metabolites from Aspergillus spp using ethyl acetate Alternate Protocol 3 : High‐volume metabolite extraction using ethyl acetate Alternate Protocol 4 : Extracting secondary metabolites from Aspergillus spp in liquid medium Support Protocol : Creating an overlay culture Basic Protocol 4 : Extracting DNA from filamentous fungi Basic Protocol 5 : Creating a DNA construct with double‐joint PCR Alternate Protocol 5 : Creating a DNA construct with yeast recombineering Basic Protocol 6 : Transformation of Aspergillus spp Basic Protocol 7 : Co‐culturing fungi and bacteria for extraction of secondary metabolites